การพัฒนาโปรแกรมปรับเปลี่ยนพฤติกรรมโดยประยุกต์แนวคิดการบำบัดด้วยการแก้ไขปัญหาร่วมกับแนวคิดการบำบัดด้วยการออกกำลังกายเพื่อลดภาวะซึมเศร้าของนักเรียนมัธยมศึกษาตอนต้น - โสภา ช้อยชด (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purposes of this research were to: 1) develop a causal model of depression of lower secondary school students, 2) examine the goodness of fit of the model with empirical data, 3) develop a behavior modification program applying problem-solving therapy with exercise therapy to reduce depression levels among lower secondary school students, and 4) determine the effectiveness of a behavior modification program applying problem-solving therapy with exercise therapy to reduce depression levels among lower secondary school students. Samples were 4,089 lower secondary school students. The Depression Causes Questionnaire (DCQ) and the Thai version of the Patient Health Questionnaire for Adolescents (PHQ-A) were employed to collect the data. Data were analyzed using descriptive statistics and confirmatory factor analysis by Mplus. Program effectiveness was assessed using 16 lower secondary school students. Data were analyzed using descriptive statistics and repeated measures ANOVA. The results were as follows: 1) The causal model of depression of lower secondary school students consisted of 4 components, i.e., self-factor, family factor, friendship and romantic intimacy factor, and social factor. 2) The causal model of depression of lower secondary school students fitted with the empirical data (chi-square = 97.630, p-value = .088, CFI = 0.999, TLI = 0.997, RMSEA = 0.009, SRMR = 0.014). The self-factor and family factor had statistically significant influence on depression among lower secondary school students, whereas the friendship and romantic intimacy factor along with social factor did not have a statistically significant influence on depression among lower secondary school students. 3) The developed program consisted of eight activities. The program was rated in the most suitable level. 4) Repeated measures ANOVA revealed that the program significantly decreased depression levels at post-treatment and at one-month follow-up.